Drunkards and Singers: A Mongolian Battle of Sounds - Laurent Legrain (Journal of Ethnology and Folkloristics)
When I conducted fieldwork among the Darhad of northern Mongolia my informants repeatedly asserted that after a good singer’s performance even the most badly intoxicated lad stands still and keeps silent. In this article, I make three points in order to explain why this claim was made. In the first one, I show that the main concern about singing performance at social gatherings is not about revealing the singer’s inner emotional realm but rather about crafting a collective feeling that has the ability to make people temporarily shed their otherness and converge. The problem with drunkards lies in the fact that they are unable to participate and even noisily impede this rite of convergence. The main reason is that they are not sufficiently detached from their own inner realm. I then put the concept of noise in context, arguing that it forms the repulsive pole of a Mongolian sonic continuum. In my last point, I stress the fact that according to Mongolian linguistic ideology, noise brings misfortune to the entire community. That is why good singers must win their battle against drunkards.